Preparation and Characterization of Acrylic Acid-Ca-Montmorillonite and Its Application for Preparation of Poly(vinyl acetate)/Montmorillonite Nanocomposite Emulsion by in situ Emulsion Polymerization - Wang, J.; Liu, Z.Y. (Asian Journal of Chemistry, 2013)
The materials of acrylic acid-Ca-montmorillonite were synthesized by dehydration reaction between the ethanol/cyclohexane mixed solvent of the reactants of acrylic acid and the cyclohexane solution of alkaline calcium base montmorillonite (acid-activated montmorillonite, calcium oxide and deionized water). The hybrids were characterized by fourier transformation infrared spectroscopy (FT-IR), wide angle X-ray powder diffraction (WXRD), thermogravimetric (TG) analysis. FT-IR analysis showed carboxyl group (-COOH) of acrylic acid reacted with hydroxyl group (-OH) of Ca-montmorillonite. WXRD analysis showed that acrylic acid intercalated the montmorillonite and the basal spacing increased from 1.39 nm of acid-activated montmorillonite to 1.6 nm of acrylic acid-Ca-montmorillonite. Thermogravimetric analysis showed that the thermal stability of organo-montmorillonite enhanced. Influences of synthetic parameters in the experiment were studied in detail. According to single factor analysis of synthetic parameters, the optimum preparation conditions was 5 g Ca-montmorillonite, 5 g acrylic acid, 50 mL hexamethylene as dispersing agent, 60 mL ethanol/hexamethylene solution (8:52, volume ratio), reaction time 3 h, stirring rate 150 r/min. The poly(vinyl acetate)/montmorillonite nanocomposite emulsion was prepared by in site intercalative emulsion polymerization of vinyl acetate in the presence of organo-montmorillonite. The wide angle X-ray powder diffraction results demonstrated that the montmorillonite was exfoliated during polymerization. The bonding power of the nanocomposite emulsion of containing 3 % organo-montmorillonite was the best one.